The role of cocoa in Ghana's future development: Do geography and ethnic diversity matter? - Breisinger, Clemens; Diao, Xinshen; Kolavalli, Shashidhara; Thurlow, James (International Food Policy Research Institute, 2008)
The recent surge in world commodity prices might alter the role of traditional export crops in African economies. While export crops have traditionally been important sources of foreign exchange earnings and government revenues, Ghana is an exceptional case, where a combination of favorable external conditions and internal reforms have made cocoa the driver of growth and poverty reduction. Cocoa's share of agricultural GDP has been increasing rapidly and existing yield gaps and the prospects of continued high world commodity prices suggest further growth potential. We find that increasing cocoa production by around 60,000 tons per annum is needed to support Ghana reaching its middle-income country target. However, cocoa’s poverty-growth elasticity is low, thus implying that further growth is unlikely to lead to the large reductions in poverty experienced in the past. Finally, we show that, even with complimentary growth in other sectors, cocoa will continue to dominate agricultural exports over the medium term and that structural diversification remains a key challenge for Ghana.